POVERTY REDUCTION AND SUSTAINABLE DEVELOPMENT IN NIGER DELTA REGION OF NIGERIA: STRATEGIES FOR COUNSELLING - A.D, OGHIAGBEPHAN, (IJRDO - Journal of Applied Management Science, 2016)
The Niger Delta region of Nigeria is richly endowed with huge resources of petroleumoil which is a major source of National income, yet the region is characterized bypoverty. It is against this background that the present paper attempts to examine howpoverty can be reduced particularly in respect to the people through skills acquisition inthe region. Despite all the measures adopted by government at all levels to reducepoverty, a high percentage of Nigerians are still poor. The scourge seems unbolting as aresult of the negative role of globalization in the economy of Nigeria, disparities inpeoples income, gender imbalance as far as access to economic resources is concerned,disparities in access to health and education, corruption, neglect of agriculture amongothers. Be that as it may, the paper highlights some of the causes and effects of povertyin Niger delta region, discusses some approaches to poverty reduction, mentions somereduction strategies, looks at some of the problems that militated against previousNational Poverty eradication programmes and finally the author proffers somerecommendations that will help to reduce poverty in the Niger Delta Region of Nigeria.